Performing Piety and Power: The Dramaturgy of Female Leadership and Religious Authority in the Islamic Student Organization (IPPNU) - Vivin Arfiyanti; Medhy Aginta Hidayat (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
This study examines how female leaders in Ikatan Pelajar Putri Nahdlatul Ulama (IPPNU) actively construct and negotiate religious authority through everyday dramaturgical practices. Drawing on the dramaturgical perspective of Erving Goffman, this article argues that leadership in religious organizations is not merely a formal or administrative role but a performative process shaped by interaction, normative expectations, and gendered structures. Using a qualitative phenomenological approach, the study explores the lived experiences of ten female leaders at the Pimpinan Anak Cabang and Pimpinan Ranting levels in Sekaran District, Lamongan Regency. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using thematic analysis. The findings reveal that female leaders strategically engage in impression management by performing religious, communicative, assertive, and exemplary identities in public settings (front stage) to gain and sustain legitimacy. At the same time, in private settings (backstage), they express emotional fatigue, vulnerability, and more spontaneous personal identities. The study demonstrates that religious authority is collectively produced through the interaction of impression management, emotional labor, and symbolic recognition rather than merely institutional position. This study contributes to the sociology of religion and leadership by integrating dramaturgy, emotional labor, and symbolic capital to explain the production of young women’s religious authority in local Islamic organizations. It demonstrates that female leadership operates as a reflexive and negotiated social practice situated within broader gendered and socio-religious power relations.